I am investigating parameter estimation in reduced-rank regression and have come across the following linear algebra result which I haven`t been able to prove. Suppose, $A \in \mathbb{R}^{nxm}$ of full rank, $B \in \mathbb{R}^{mxm}$ symmetric positive definte and $C \in \mathbb{R}^{nxn}$ also symmetric positive definite. Consider the following general eigenvalue-eigenvector problem:
$(ABA^T)U=CUD$
where
- $U \in \mathbb{R}^{nxm}$ is the matrix such that its columns are the eigenvectors of the general eigenvalue-eigenvector problem
- $D \in \mathbb{R}^{mxm}$ is the diagonal matrix such that its entries are the eigenvalues of the general eigenvalue-eigenvector problem
Now let:
- $(U_1,D_1)$ be the solution to the problem when $B=E^{-1}$ and,
- $(U_2,D_2)$ be the solution to the problem when $B=(E-A^TC^{-1}A)^{-1}$,
- with $E \in \mathbb{R}^{mxm}$, symmetric positive definite
We know that $U_1^TU_1=U_2^TU_2=I_m$. We also know that $U_1 \neq U_2$.
I want to prove that $U_1U_1^T=U_2U_2^T$. ¿Any pointers? Thanks!
Latest: The general eigenvalue-eigenvector problem above is equivalent to the following regular eigenvalue-eigenvector problem:
$(C^{-0.5}(ABA^T)C^{-0.5})X = XD$
where
- $X \in \mathbb{R}^{nxm}$ such that $U=C^{-0.5}X$.
Now if we set $S=B^{0.5}A^TC^{-0.5}$ we have that the eigenvalue-eigenvector problem is:
$(S^TS)X=XD$
where
- $S \in \mathbb{R}^{mxn}$
- $S$ has the following singular value decomposition: $S=YD^{0.5}X^T$
- $X$ has the eigenvectors of $S^TS$ and $Y$ has the eigenvectors of $SS^T$
- $D$ has the eigen values of both $S^TS$ and $SS^T$
By considering the eigenvalues of $SS^T$ instead of those of $S^TS$ I have been able to deduce a relationship between $D_1$ and $D_2$:
$SS^T=YDY^T=B^{0.5}A^TC^{-1}AB^{0.5}$
To obtain the eigenvalues of $SS^T$ we have to solve the following general eigenvalue characteristic equation:
$| \lambda B^{-1} - A^TC^{-1}A | = 0$
If we substitute the two possible values that $B$ can take we get the following two equations:
- $|\lambda_1 E - A^TC^{-1}A|=0$
- $|\lambda_2 (E-A^TC^{-1}A) - A^TC^{-1}A|=(1+ \lambda_2)^m|(\frac{\lambda_2}{1+ \lambda_2}) (E-A^TC^{-1}A) - A^TC^{-1}A|=0$
From this we can establish that:
- $\lambda_1 = \frac{\lambda_2}{1+ \lambda_2}$, and in general
- $D_1 = D_2(I_m + D_2)^{-1}$
However, I still haven't been able to deduce a relationship between $U_1$ and $U_2$ or equivalently between $X_1$ and $X_2$ that allows me to prove that $U_1U_1^T$=$U_2U_2^T$.